ADRIAN LEVERKÜHN’S MUSICAL JOURNEY OUTLINED IN THE NOVEL DOCTOR FAUSTUS, BY THOMAS MANN / A TRAJETÓRIA MUSICAL DE ADRIAN LEVERKÜHN DELINEADA NO ROMANCE DOUTOR FAUSTO DE THOMAS MANN - Campos, Beatriz Schmidt; Barbosa, Sidney (Revista ECOS, 2016)
In this article we intend to analyze Adrian Leverkühn’s musical journey outlined in the novel Doctor Faustus by Thomas Mann, covering several aspects: Adrian’s musical influences when composing a new musical style, Theodor Adorno’s real musical reviews of  compositions, which were used by the author throughout the novel, the style of real composers who influenced Adrian in composing his own musical work,  demonstrating how the musician deeply values the relationship between music and speech. Therefore, among these references from the musical world in the fictional universe, we can highlight the embryonic process of his rigorous composition inspired on Arnold Shöenberg’s dodecaphonic music. This rigorous composition is the reason why Mephisto chooses to buy Adrian’s creative time and it also constitutes a metaphoric representation of aspects present in German mentality that shows an ambivalence between the humanistic culture and the appeal of the Faustian pact.